Latihan Kombinasi Terhadap Peningkatan Fungsi Kognitif Terhadap Peningkatan Fungsi Kognitif - Nurafriani, Elvia, Yulisna Mutia Sari, SST.FT, M.Sc (GRS) (2017)
Background: On the elderly ages, human is slowly has decreasing at some aspects including the decline of memory. The decline of memory is one of sign for decreasing of cognitive function. The decreasing of cognitive function in the form Mild Cognitive Impairment and Moderate Cognitive Impairment are transition term from the normal decreasing of cognitive function to patologic or cognitive function disorder like demensia. One of the ways for mantain the cognitive function of elderly people is with giving combined exercise such as aerobics, stretching and strengthening. Objective: To know the effect of combined exercise with cognitive function for the elderly people in Posyandu Ngudi Sehat Colomadu. Benefits:To be able to know the effect of giving the combined exercise for increasing cognitive function for elderly people. Methods: This research uses Quasi Experimental method. The sampling technique used is Purposive Sampling. The samples that collected based on inclusion and exclusion criteria is 20 people. The measurment of cognitive function before and after giving the combined practice uses Mini Mental State Examination (MMSE). The correlation test uses Wilcoxon Test with p value score is 0,000. Results: Based on Wilcoxon Test, it is known that p-value score 0,000 < 0,005 so H0 is declined and Hα is accepted.It can be interpreted that there is effect of giving combined exercise for increasing cognitive function of the elderly people. Conclusion: Giving the combined exercise for four weeks is increase cognitive function in the elderly in Posyandu Ngudi Sehat Colomadu. Keywords: Cognitive Function, Combined Exercise, MMSE, Elderly People